2017
DOI: 10.1039/c7ra05151d
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating an anionic polyacrylamide (APAM) with an anionic block structure for high turbidity water separation and purification

Abstract: ab Ultraviolet (UV)-initiated template polymerization (UTP) was used as a feasible strategy to prepare a novel anionic polyacrylamide (APAM) with a microblock structure. In the template copolymerization system, acrylamide (AM) and sodium allylsulfonate (SAS) were used as monomers, and poly Results showed that the novel anionic microblock structure was formed in the template copolymer.Besides, the results of the association constant (K M ) indicated that the copolymerization followed I Zipup (ZIP) template poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…For the APAM, the peaks at 3423 cm −1 and 3198 cm −1 were due to–NH 2 stretching vibrations, the peak at 1666 cm −1 was the characteristic absorption peak of the carbonyl group. The peak at 1617 cm −1 was due to the amide II (N–H) bending vibration [ 28 , 33 ]. What is more, the peaks at 1178 cm −1 and 1119 cm −1 were associated with C–N stretching vibration [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the APAM, the peaks at 3423 cm −1 and 3198 cm −1 were due to–NH 2 stretching vibrations, the peak at 1666 cm −1 was the characteristic absorption peak of the carbonyl group. The peak at 1617 cm −1 was due to the amide II (N–H) bending vibration [ 28 , 33 ]. What is more, the peaks at 1178 cm −1 and 1119 cm −1 were associated with C–N stretching vibration [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to overcome such shortcoming, GO and Anionic polyacrylamide (APAM) complexes were first prepared in this article. APAM has functional groups with adsorption properties such as an amide group or a carboxyl group, and exhibits an electronegativity, which can lower the potential of the metal cation, and provide favorable ion adsorption capacity [ 26 , 27 , 28 ]. APAM can bridge between particles in water to concentrate particles and form floc deposits, which allows it to be used as a flocculant [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed that the template PAAS has a significant effect on the R P and polymer conversion, and the template polymerization mechanism follows the typical (I) ZIP. [29] Because PAAS has the opposite charge to DMC, it can arrange and assemble DMC by electrostatic attraction. The cationic monomers adsorbed and sequentially arranged on the template PAAS can form the precursor of the cationic fragment structure.…”
Section: Effect Of N Paas :N Dmcmentioning
confidence: 99%
“…Anionic polyacrylamide (APAM) is a widely used organic polymer flocculent in tailings thickening and shows good performance and high efficiency at low cost, particularly in the treatment of fine particles [9,10]. For thickened tailings slurries in pipeline transportation, groups of shear tests were conducted, and the variation curves of rheological parameters were obtained.…”
Section: Introductionmentioning
confidence: 99%